2018
DOI: 10.3168/jds.2017-13351
|View full text |Cite
|
Sign up to set email alerts
|

Varying the ratio of Lys:Met while maintaining the ratios of Thr:Phe, Lys:Thr, Lys:His, and Lys:Val alters mammary cellular metabolites, mammalian target of rapamycin signaling, and gene transcription

Abstract: Amino acids are not only precursors for but also signaling molecules regulating protein synthesis. Regulation of protein synthesis via AA occurs at least in part by alterations in the phosphorylation status of mammalian target of rapamycin (mTOR) pathway proteins. Although the ideal profile of Lys:Met to promote milk protein synthesis during established lactation in dairy cows has been proposed to be 3:1, aside from being the most-limiting AA for milk protein synthesis, the role of Met in other key biologic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
70
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(82 citation statements)
references
References 48 publications
10
70
0
Order By: Relevance
“…Thus, the levels of Met and Arg used in the present study were in accordance with our previous work. 16,17 Within those in vitro studies, although there was an overall positive effect on mammary cell metabolism, the negative effects on phosphorylation of 4E binding protein 1 (EIF4EBP1), eukaryotic elongation factor 2 (EEF2), 16 mTOR, 17 and mRNA abundance of β-casein and AA transporters 17 were partly consistent with the present results. Similarly, despite using EAA profiles similar to those in IPAA, previous in vivo studies also reported results contrary to ours, for instance phosphorylation ratio of ribosomal protein S6 (RPS6) was lower at a Lys : Met = 2.9 : 1 41 and milk protein synthesis or the efficiency of N utilization was not modified at an Lys : Arg = 2 : 1.…”
Section: Food and Function Papersupporting
confidence: 90%
See 3 more Smart Citations
“…Thus, the levels of Met and Arg used in the present study were in accordance with our previous work. 16,17 Within those in vitro studies, although there was an overall positive effect on mammary cell metabolism, the negative effects on phosphorylation of 4E binding protein 1 (EIF4EBP1), eukaryotic elongation factor 2 (EEF2), 16 mTOR, 17 and mRNA abundance of β-casein and AA transporters 17 were partly consistent with the present results. Similarly, despite using EAA profiles similar to those in IPAA, previous in vivo studies also reported results contrary to ours, for instance phosphorylation ratio of ribosomal protein S6 (RPS6) was lower at a Lys : Met = 2.9 : 1 41 and milk protein synthesis or the efficiency of N utilization was not modified at an Lys : Arg = 2 : 1.…”
Section: Food and Function Papersupporting
confidence: 90%
“…The modified lactogenic media was prepared according to . 17,33 The 10 EAA (L-isomer, Sigma-Aldrich, St Louis, MO) were individually added into the custom highglucose DMEM (devoid of these 10 EAA, custom made from Gibco, Carlsbad, CA). Treatment media were prepared by increasing only Met, Arg or both while keeping the concentrations of 7 other EAA (histidine, isoleucine, leucine, phenylalanine, threonine, tryptophan, valine) the same across all media (Table 1).…”
Section: Treatments and Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…The Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 18 October 2018 doi:10.20944/preprints201810.0411.v1 effect of increasing supplemental Met according to the ideal 3:1 Lys to Met ratio related to protein synthesis and mTOR pathway-related proteins phosphorylation status has also been determined recently [112]. Using gas chromatography-mass spectrometry metabolomics, that study revealeddistinct clusters of metabolites that were differentially concentrated in response to different Met-Lys ratios [112].…”
Section: Metabolomicsmentioning
confidence: 99%